Application of allergic rhinitis and its impact on asthma guidelines in terms of classification, risk factors, quality of life and co-morbidities in allergic rhinitis patients in Northern India - Agarwal, Anmol Kumar; Sharma, Rohit; Sharma, Vinit (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Despite the high prevalence of allergic rhinitis, there are only few studies on application of ARIA (allergic rhinitis and its impact on asthma) guidelines. Methods: It was a prospective study of 164 patients. Based on ARIA guidelines; patients were graded for severity, risk factors studied, co morbidities documented and quality of life assessed using rhinoconjunctivitis quality of life questionnaire (RQLQ). Results: A total of 164 cases were studied between the age group 10-72 years of which 56.1% were males. Most common trigger observed was dust (56.1%). Allergic conjunctivitis was most common co-morbidity associated. Using RQLQ it was observed that ARIA. Conclusions: ARIA guidelines appropriately classify allergic rhinitis, determines risk factors and associated co-morbidities. RQLQ can be used to determine quality of life in allergic rhinitis.